Efficient degradation of organic pollutants using peroxydisulfate activated by magnetic carbon nanotube - Yawei Shi; Yi Zhang; Guobin Song; Liya Tong; Ya Sun; Guanghui Ding (Water Science and Technology, 2022)
The magnetic composite of Fe3O4 and carbon nanotube (MCNT) was fabricated in a facile one-pot solvothermal method and employed to activate peroxydisulfate (PDS) for degradation of Rhodamine B (RhB) and other pollutants. The effects of operational factors including MCNT dosage and PDS dosage were studied, and high removal efficiencies of 84.2–99.5% were achieved for these pollutants with 0.3 g/L MCNT and 4 mM PDS. The effects of environmental factors including initial pH, inorganic cations, inorganic anions, humic acid and water matrix were also studied. Reusability test showed that the removal efficiency declined in four consecutive runs, which was attributed to the adsorbed oxidation products on the catalyst surface. Based on quenching experiments, solvent exchange (H2O to D2O), inductively coupled plasma and open circuit potential tests, it was concluded that radicals of ·OH/SO4·− and the non-radical electron-transfer pathway were involved in the MCNT/PDS system, and the contributions of O2·−, 1O2, high-valent iron-oxo species and homogenous activation were insignificant. Moreover, the orbital-weighted Fukui functions of RhB were calculated by density functional theory, and its plausible degradation pathway was proposed based on the calculation results. Finally, toxicity evaluation of the degradation products was performed in the quantitative structure-activity relationship approach. HIGHLIGHTS RhB and other organic pollutants were efficiently degraded with the MCNT/PDS system.; OH, SO4·− and the non-radical electron-transfer pathway were mainly responsible.; The degradation pathway was proposed based on LC-MS and DFT calculations.; Toxicity evaluation of the degradation products was performed using ECOSAR.;